Impact of a plant extract on the viability of yogurt starter and probiotic cultures in nonfat yogurt - Michael, Minto (Kansas State University, 2010)
Yogurt starter and probiotic bacteria have been reported to confer health benefits to the consumer; however, to confer these health benefits yogurt and probiotic bacteria should be live and present at the recommended concentration of 6 to 8 log cfu g-1. Cegemett® Fresh (Cognis Nutrition & Health, Monheim, Germany) is a plant extract that possesses antioxidant properties. This research was divided into two experiments. The objective of experiment-I was to investigate the effect of plant extract supplementation on the redox potential (Eh) and the viability of starter cultures (Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus) in nonfat yogurt. Five yogurt samples [non-supplemented, supplemented with 0.5 or 1.0% (w/v) plant extract, or supplemented with 0.014 or 0.028% (w/w) L-cysteine.HCl] were prepared, stored at 5ºC for 50 days and analyzed weekly. L. bulgaricus counts in supplemented yogurts were > 6 log cfu mL-1 for additional 7 to 21 days compared with non-supplemented yogurt; however, S. thermophilus counts in all yogurts were > 6 log cfu mL-1 throughout the storage. Overall, Eh of plant extract supplemented yogurts were similar to non-supplemented yogurt during storage; therefore the improvement in L. bulgaricus viability cannot be attributed to the Eh alone. The objective of experiment-II was to investigate the effect of plant extract supplementation on the buffering ability of the yogurt mix, and on the viability of starter and probiotic (Bifidobacterium animalis ssp. animalis and Lactobacillus acidophilus) cultures in nonfat yogurt stored at 5ºC for 50 days. Nine yogurt samples were prepared with 0.5% (w/v) plant extract, 0.25% (w/v) sodium acetate or no supplement, fermented with starter cultures and B. animalis, L. acidophilus or both probiotics, and analyzed weekly. The plant extract and sodium acetate supplemented yogurt mixes had greater buffering capacities compared with non-supplemented yogurt mix. L. bulgaricus and L. acidophilus counts in supplemented yogurts were > 6 log cfu mL-1 for additional 7 to 35 days compared with non-supplemented yogurts. S. thermophilus and B. animalis counts were not affected by supplementation. These results suggested that greater buffering capacity could improve the viability of L. bulgaricus and L. acidophilus in yogurt during storage.
Keywords: Yogurt; Probiotic; Redox potential; Buffering capacity; Agriculture, Food Science and Technology (0359)